ChemInform Abstract: (—)‐Isosteviol as a Versatile Ex‐Chiral‐Pool Bulding Block for Organic Chemistry. Issue 48 (26th November 2013) - Lohoelter, Christina; Weckbecker, Magdalena; Waldvogel, Siegfried R.
Abstract Review: 82 refs.